A Split-Luciferase-Based Trimer Formation Assay as a High-throughput Screening Platform for Therapeutics in Alport Syndrome. Issue 5 (17th May 2018) - Omachi, Kohei; Kamura, Misato; Teramoto, Keisuke; Kojima, Haruka; Yokota, Tsubasa; Kaseda, Shota; Kuwazuru, Jun; Fukuda, Ryosuke; Koyama, Kosuke; Matsuyama, Shingo; Motomura, Keishi; Shuto, Tsuyoshi; et al.
Summary: Alport syndrome is a hereditary glomerular disease caused by mutation in type IV collagen α3–α5 chains (α3–α5(IV)), which disrupts trimerization, leading to glomerular basement membrane degeneration. Correcting the trimerization of α3/α4/α5 chain is a feasible therapeutic approach, but is hindered by lack of information on the regulation of intracellular α(IV) chain and the absence of high-throughput screening (HTS) platforms to assess α345(IV) trimer formation. Here, we developed sets of split NanoLuc-fusion α345(IV) proteins to monitor α345(IV) trimerization of wild-type and clinically associated mutant α5(IV). The α345(IV) trimer assay, which satisfied the acceptance criteria for HTS, enabled the characterization of intracellular- and secretion-dependent defects of mutant α5(IV). Small interfering RNA-based and chemical screening targeting the ER identified several chemical chaperones that have potential to promote α345(IV) trimer formation. This split luciferase-based trimer formation assay is a functional HTS platform that realizes the feasibility of targeting α345(IV) trimers to treat Alport syndrome. Graphical Abstract: Highlights: Mutant α5(IV) monomers are stable intracellularly despite harboring a mutation α345 (IV) trimer is a preferred therapeutic target for Alport syndrome Developing HTS-applicable α345 (IV) trimer assay Several chemical chaperones have potential to promote α345(IV) trimer formation Abstract : Omachi et al. showed that the type IV collagen α345(IV) trimer is a therapeutic target for the hereditary kidney disease, Alport syndrome. They established an HTS-applicable α345(IV) trimer assay and showed that chemical chaperones rescued trimer formation of mutant α5(IV).